The Acceptance of Covid-19 Vaccine in North Sulawesi Community: Prevalance and Risk Factor - Nelwan, Jeini Ester; Sumampouw, Oksfriani Jufri; Ticoalu, Jansje Vera; Musa, Ester Candrawati; Ottay, Ronald Imanuel (MultiTech Publisher, 2024)
Vaccination stands as the sole preventive measure against the transmission of COVID-19. The vaccination rollout in Indonesia comprises three stages: primary vaccinations 1 and 2, along with an additional 3rd or booster vaccination. However, certain regions still exhibit a stage 2 vaccination coverage below 70%. Various factors, including age and gender, impact the acceptance of the Covid-19 vaccine. The objective of this study was to scrutinize the association between age, gender, and the acceptance of Covid-19 vaccination in the jurisdiction of the Kawangkoan Barat Public Health Center. Conducted between February and July 2022, this correlational research involved 400 respondents aged 18 and above. The study variables encompassed age, gender, and vaccination acceptance, assessed through a fill-in sheet. Bivariate data analysis employed the chi-square test, revealing a significant correlation between age and vaccination acceptance. The prevalence ratio (PR) of 1.504 indicated that individuals aged 18-59 years were 1.504 times more likely to have incomplete vaccinations. However, gender did not exhibit a significant correlation with vaccination acceptance. In conclusion, age emerges as a correlated factor influencing the acceptance of Covid-19 vaccination